Rekayasa Proses Ekstraksi Nira Tebu (Saccaharum officinarum L.) Menggunakan Enzim Selulase Dan Xilanase - Rusdianto, Andree Setiawan; Wardani , Herlina Rima (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Sugarcane (Saccharum officinarum L.) is a seasonal crop processed into white crystal sugar. The juice extraction process is carried out by milling the sugarcane, during which the plant cells are easily ruptured to maximize juice release. This process takes place in a diffuser carriage equipped with 12 trays, serving as extraction chambers between the juice and the crushed bagasse. Enzyme addition is applied to degrade Structural components of the cell wall, thereby accelerating juice release. This study aimed to investigate the effect of extraction time and enzyme type on the yield and characteristics of sugarcane juice, as well as to determine the optimal combination of these factors to produce juice with favorable properties, including yield, pH, brix, pol, viscosity, juice color, and purity (HK). The best treatment was determined using the De Garmo method, while data were analyzed using ANOVA and DMRT at a 95% confidence level. Observed parameters included juice yield, pH, brix, pol, viscosity, color, and HK. Results showed that extraction time and enzyme type significantly affected pH, brix, pol, viscosity, and color attributes (L*, a*, b*, chroma, hue), but had no significant effect on juice yield and HK. The best treatment (A1X1), involving cellulase addition for 10 minutes, yielded 72.13% juice, 9.29% pol, 12.68% brix, and 73.27% HK. This treatment was proven effective in enhancing sugarcane juice extraction.